Frequency of chromosomal aberrations in Prague mothers and their newborns - Rossnerova, A; Balascak, I; Rossner, P; Sram, R J (Mutation research, 2010)
The capital city of Prague is one of the most polluted areas of the Czech Republic. The impact of air pollution on the level of chromosomal aberrations was systematically studied: analyses were performed using fluorescence in situ hybridization (FISH) with whole-chromosome painting for chromosomes #1 and #4. In the present study, we analyzed the levels of stable (one-way and two-way translocations) and unstable (acentric fragments) chromosomal aberrations in 42 mothers living in Prague and in their newborns. The average age of the mothers was 29 years (range, 20-40 years). Blood samples were collected from October 2007 to February 2008. The average levels of carcinogenic polycyclic aromatic hydrocarbons (c-PAHs) and benzo[a]pyrene (B[a]P) in respirable particles (PM2.5), as determined by stationary monitoring, were 21.0+/-12.3 ng/m(3) and 2.9+/-1.8 ng/m(3), respectively. We did not observe any effect of either c-PAH or B[a]P exposure on the genomic frequency of translocations (per 100 cells, F(G)/100) in either group due to their similar exposure during the winter months. The mean values of F(G)/100 representing stable aberrations were 0.09+/-0.13 vs 0.80+/-0.79 (p<0.001) for newborns vs mothers, indicating a significant increase of F(G)/100 with age. On the other hand, the frequency of unstable aberrations did not differ between the two groups. Our results demonstrate how the patterns of different types of aberration differed between newborns and mothers: we observed 64.3% unstable aberrations and 35.7% stable aberrations in newborns vs 19.7% and 80.3% in mothers, respectively. Our results indicate that after birth the frequencies of aberrations are very low and that the aberrations are represented mainly by acentric fragments. The changes observed in mothers show a shift to stable aberrations represented mainly by two-way translocations. The mother's age affected the level of aberrations in newborns: the group of children born to older mothers (31-40 years) had significantly increased F(G)/100 levels.
Keywords: dospělí; Female; matka - expozice noxám; novorozenec; Adult; ženské pohlaví; Maternal Exposure; fetální krev; malování chromozomů; lidé; Infant, Newborn; Translocation, Genetic; Chromosome Painting; těhotenství; mutageny; Fetal Blood; Air Pollutants; chromozomální aberace; Czech Republic; polycyklické aromatické uhlovodíky; Polycyclic Aromatic Hydrocarbons; věk matky; Česká republika; hybridizace in situ fluorescenční; Mutagens; translokace genetická; In Situ Hybridization, Fluorescence; Maternal Age; látky znečišťující vzduch; Pregnancy; Chromosome Aberrations; Humans